Single nucleotide polymorphisms in carnosinase genes (CNDP1 and CNDP2) are associated with power athletic status - Limongi França Guilherme, J. P.; Lancha Jr, A. H. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Carnosine (ß-alanyl-L-histidine), abundantly found in skeletal muscle, plays an important role during exercise, especially for high-intensity contractions. Variability in muscle carnosine content between individuals exists and may also be explained by different genetic bases, although no study has addressed the association of polymorphisms in genes related to carnosine metabolism in athletes. This study aimed to investigate the frequency of single nucleotide polymorphisms (SNPs) in the carnosinase genes (CNDP1 and CNDP2) in a large Brazilian cohort of athletes and nonathletes. Eight SNPs were compared between a representative cohort of elite athletes from Brazil (n = 908) and a paired group of nonathletes (n = 967). The athletes were stratified into three groups: endurance (n = 328), power (n = 415), and combat (n = 165). The CNDP2 rs6566810 (A/A genotype) is overrepresented in endurance athletes, but only in international-level endurance athletes. Three SNPs (CNDP2 rs3764509, CNDP2-CNDP1 rs2346061, and CNDP1 rs2887) were overrepresented in power athletes compared with nonathletes. Carriers of the minor allele had an increased odds ratio of being a power athlete. For the rs2346061, no significant difference was observed in genotype frequencies between power and combat sports athletes, but for rs2887 the power and combat groups showed an inverse genotype distribution. In conclusion, we found that minor alleles carriers for CNDP2 rs3764509 (G-allele), CNDP2-CNDP1 rs2346061 (C-allele), and CNDP1 rs2887 (A-allele) are more likely to be a power athlete. These polymorphisms may be novel genetic markers for power athletes. Furthermore, these results are suggestive of a distinct CNDP genotype for sporting development.